2017
DOI: 10.1002/jmv.24992
|View full text |Cite
|
Sign up to set email alerts
|

Presence of infection and analysis of HPV subtypes in girls younger than 9 years old attended at a referral service in Espírito Santo, Brazil

Abstract: Human papillomavirus (HPV) is found in adults and adolescents and is associated with genital warts and cervical cancer. However, it has been detected in girls younger than 10 years old. Currently, there are no prevention methods for this age group, since it is not considered a risk group. The aim of this study was to evaluate the presence of infection and HPV subtype in girls under 9 years old attended at a referral service in the State of Espírito Santo, Brazil. Forty-three girls younger than 9 years old had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
1
1
Order By: Relevance
“…We wish to emphasise that the prevalence of antibodies among the children participating in our study may be considerably higher than values reported elsewhere [27, 28]. Also, our results showed that boys aged 9–14 years had a higher HPV18 seroprevalence than other studies.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…We wish to emphasise that the prevalence of antibodies among the children participating in our study may be considerably higher than values reported elsewhere [27, 28]. Also, our results showed that boys aged 9–14 years had a higher HPV18 seroprevalence than other studies.…”
Section: Discussioncontrasting
confidence: 58%
“…A study conducted in Brazil reported the presence of high-risk HPV serotypes in girls and boys aged 10–15 years, with a seroprevalence of 9.3% for HPV-16 and 1.9% for HPV-18 [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HPV can certainly be acquired at an early age: One of 34 children (a male, aged 9), followed up after one year, was found positive for HPV18. Sartori et al also reported the presence of HPV infection in girls under 9 years of age. Acquisition of HPV at an early age supports the recommendation that HPV vaccination should be done at the age of 9.…”
Section: Discussionmentioning
confidence: 92%
“…The products of PCR amplification reactions, performed in triplicates on a T100 ™ Thermal Cycler (Bio‐Rad), were resolved on 2% agarose (0.5 µg/mL EtBr) horizontal gel electrophoresis using a 1X TAE buffer system, and DNA bands were visualized using an UV gel documentation system (AlphaImager HP System, Protein Simple). The presence of HPV viral DNA was assessed by conventional PCR using degenerate primers MY09 and MY11 (Table ) targeting the L1 gene (HPV species) in reaction mixture composing nuclease‐free water, Taq buffer (1X), MgCl 2 (1.5 mmol/L), dNTPs (0.2 mmol/L), primers (0.4 µmol/L), DNA (60 ng), and Taq polymerase (1 U); the thermocycling steps were as follows: (a) initial denaturation: 95°C for 5 minutes; (b) 40 cycles of denaturation (95°C for 1 minute), annealing (56°C for 1 minute) and extension (72°C for 1 minute); and (c) final extension: 72°C for 10 minutes. Subsequently, a nested PCR assay was carried out using GP05+ and GP06+ specific primers (Table ), targeting the L1 amplicons amplified using MY09/MY11, for confirming the presence of HPV DNA using the reaction mixes comprising nuclease‐free water, Taq buffer (1X), MgCl 2 (1.5 mmol/L), dNTPs (0.2 mmol/L), primers (0.4 µmol/L), Taq polymerase (1 U), and DNA template (5 µL amplification product of MY09/MY11); the thermocycling steps were as follows: (a) initial denaturation: 95°C for 5 minutes; (b) 40 cycles of denaturation (95°C for 1 minute), annealing (45°C for 1 minute) and extension (72°C for 1 minute); and (c) final extension: 72°C for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%